Flows of raw materials and food safety of products of Slovenian manufacturers after EU entry - Tomše, Romana (Sanitarno inženirstvo, 2012)
In food production, the choice of suppliers and raw materials is very important and plays a key role in providing quality, appropriate healthy food. Selection of new suppliers and the planned verification of existing suppliers is also the key point in the HACCP system (Hazard Analysis Critical Control Point, which means the risk analysis and critical control points). The aim of our survey was to analyse the level of food safety in Slovenia before and after Slovenia joined the EU. The aim of our survey was to determine whether joining the EU had an impact on choice of food suppliers and control of the raw materials used in production of foods. The common thread of research was a comparison of answers, for periods before and after Slovenia joined the EU, gained from the survey of the Slovenian food producers. The study has shown that after joining the EU there were some replacements of suppliers, as well as changes in control of suppliers, but the changes were smaller than expected. The analysis of the responses from the survey shows that the Slovenian manufacturers mostly trust domestic suppliers of raw materials. After Slovenia's accession to the EU, the use of raw materials from other EU countries, as well as the control over suppliers, has increased. After Slovenia's accession to the EU, the percentage of those Slovenian producers who control Slovenian supplier under looser criteria, has slightly increased, while the percentage of those Slovenian producers who control EU supplier under looser criteria has significantly increased. The survey results show partial distrust of free movement of goods. Producers on average partly agree that they equally trust the manufacturers in all EU member states.
Keywords: živila; živilska industrija; Slovenia; Slovenija; EU; kontrola kvalitete; nadzor nad živili; analiza; primerjave